Photocatalytic synthesis of gold nanoparticles using TiO2 nanorods: a mechanistic investigation. Issue 34 (20th August 2019) - Lu, Qipeng; Zhu, Lijie; Han, Sumei; Hou, Yanbing; Cao, Wenbin
Abstract : Herein, we investigate the mechanism of photocatalytic synthesis of noble metal nanoparticles by reductive photoelectrons generated from semiconductors. Abstract : Herein, we investigate the mechanism of photocatalytic synthesis of noble metal nanoparticles by reductive photoelectrons generated from semiconductors. To slow down the reaction rate for real-time mechanistic study, oleic acid-capped TiO2 nanorods served as photocatalysts, and chloroauric acid dissolved in oleylamine acted as the gold precursor. Based on the experimental results from the in situ absorption spectrum and corresponding TEM image, we could clarify the photoreduction mechanism: the TiO2 nanorods generate electrons under UV irradiation and provide catalytic centers for the nucleation of gold nanoparticles. Subsequently, the seeded growth of Au nanoparticles is mainly assisted by TiO2 nanorods with continuous reduction of the gold precursor. Interestingly, the separation of Au nanoparticles from TiO2 nanorods could be clearly observed. This proposed reaction mechanism may provide a convenient understanding of the photocatalytic synthesis of noble metal nanoparticles by semiconductors.